Sociodemographic and behavioral factors related to obesity among adults in the Republic of Palau based on the WHO STEPwise approach to NCD risk factor surveillance 2011-2013: A cross-sectional study - Miyuki Hasegawa; Kaori Honjo; Chifa Chiang; Takashi Mita; Berry Moon Watson; Edolem Ikerdeu; Sherilynn Madraisau; Hiroshi Yatsuya; Atsuko Aoyama; Hiroyasu Iso (Komiyama Printing Co. Ltd, 2023)
Background: Pacific islanders face drastic increase of obesity-related noncommunicable disease (NCD) due to lifestyle shifts of unhealthy diets and physical inactivity. To date, however, obesity related factors have not been well elucidated in Republic of Palau. This study aimed to investigate sociodemographic and behavioral factors related to obesity using the national level data in Palau. Methods: This is a cross-sectional, population-based study analyzing random sampling data of 2133 adults aged 25-64 years (of 20 thousand national population) from the WHO STEPwise approach to NCD risk factor surveillance (STEPS) implemented between 2011 and 2013. Sociodemographic and behavioral factors were obtained by the STEPS standardized questionnaire for NCD risk factors plus the question on betel nut chewing because of its common behavior in Micronesian countries. Logistic regression analysis was performed to estimate multivariable odds ratio (OR) of general obesity (body mass index ≥30.0 kg/m2) and central obesity (waist circumference ≥90 cm in men and ≥80 cm in women). Results: Means of body mass index, prevalence of general obesity and central obesity were higher in women (29.9 kg/m2, 45.5% and 85.4%) than in men (29.3 kg/m2, 40.4% and 67.6%). After adjusted by other potential factors, native Palauan (OR 4.4, 95% CI, 2.7-7.0 for men and 3.6, 2.3-5.6 for women), betel nut chewing (1.5, 1.1-2.1 for men and 1.6, 1.2-2.3 for women), men who work at government office (1.6, 1.2-2.1), women with higher household income (1.4, 1.0-1.8) were positively associated with general obesity, while frequent vegetable intake were inversely associated with it among women (0.71, 0.54-0.93). Similar associations were observed between the aforementioned factors and central obesity. Conclusions: Native Palauan, people with betel nut chewing behavior, government employment and higher income appeared to be associated with obesity, while frequent vegetable consumption were inversely associated with obesity. Further interventions for prevention and control of obesity are necessary through the enhancing public relation activities to understand harmful health effects on betel nuts chewing and recommending domestic production of vegetables.